Vipassana meditation on anxiety state, depression and quality of life of professionals in social isolation in the lockdown period -2020/COVID-19 - Sousa, Carlos Anderson Assis de; Vale, Rodrigo Gomes de Souza; Oliveira, Lia Monteiro de; Vale, Joyce Karen Lima; Drigo, Alexandre Janotta [UNESP]; Pernambuco, Carlos Soares; Borba-Pinhciro, Claudio Joaquim (Federacion Espanola Asoc Docentes Educacion Fisica-feadef, 2022)
The objective of this study to evaluate the effects of Vipassana meditation (VM) program on the state of anxiety, depression and quality of life (QoL) of professionals in social isolation during the Lockdown period in pandemic COVID19/2020. This is an experimental study with intervention based in VM exercises with pre -and post-test measures of experimental and control groups, with simple randomization. VM is a training in attention and awareness, aiming to keep mental processes under voluntary control, developing skills such as calm, concentration and focus. Fifteen sessions of VM were held, lasting from 5 -10 minutes/session. The results showed improvement in the scores of depression ( increment % =-47.6%), anxiety ( increment %=-47.7%) and QoL indicators ( increment %= 9.53), during the lockdown COVID-19/2020. It was concluded that MV was effective for all variables studied in comparison with the control group. Improvements were observed in state of anxiety and depression, in the physical domains, psychological and social relationships, as well in the perception of general QoL of participants who performed the VM in period with 15 days of Lockdown in pandemic COVID19/2020.
Keywords: Meditation; Mental health; Lockdown; Pandemic; COVID-19